2003
DOI: 10.4049/jimmunol.171.3.1328
|View full text |Cite
|
Sign up to set email alerts
|

B Cell Receptor-Mediated Syk-Independent Activation of Phosphatidylinositol 3-Kinase, Ras, and Mitogen-Activated Protein Kinase Pathways

Abstract: The Syk tyrosine kinase is a key molecule in the development of the B cell lineage and the activation of B lymphocytes after Ag recognition by the B cell Ag receptor (BCR). Several genetic studies with chicken B cells have reported that the recruitment of Syk by BCR is essential for activation of a cascade of signaling molecules including phosphatidylinositol 3-kinase, mitogen-activated protein kinases, Ras signaling pathways, phospholipase C-γ2 activation, and calcium mobilization. The identification of a Syk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…ERK was not required for this process, which is in agreement with a previous finding in SYK-deficient mice that activation of the Ras and MAPK pathway can be independent of SYK. 22 We have also shown that the phospho-flow assays can be applied to freezethawed primary lymphoma specimens that demonstrated differential signaling responses to the SYK inhibitor. Together with the data on cell line sensitivities, the profiles of PLC␥2 and AKT showed promise as in vitro biomarkers to predict clinical responses of DLBCL to SYK inhibition.…”
Section: Discussionmentioning
confidence: 89%
“…ERK was not required for this process, which is in agreement with a previous finding in SYK-deficient mice that activation of the Ras and MAPK pathway can be independent of SYK. 22 We have also shown that the phospho-flow assays can be applied to freezethawed primary lymphoma specimens that demonstrated differential signaling responses to the SYK inhibitor. Together with the data on cell line sensitivities, the profiles of PLC␥2 and AKT showed promise as in vitro biomarkers to predict clinical responses of DLBCL to SYK inhibition.…”
Section: Discussionmentioning
confidence: 89%
“…Thereafter, Syk binds the dually Src-phosphorylated ITAM [5,24] and plays a critical role in the activation of many downstream signaling enzymes such as phospholipase Cc, PI3 K and MAPK, some of which have been related to other internalization processes (i.e. receptor-mediated phagocytosis, [25,26]). Therefore, the effect of Syk inhibition on BCR-mediated Ag internalization was determined using the Syk inhibitor piceatannol [27].…”
Section: Resultsmentioning
confidence: 99%
“…The JeKo‐1 cell line, bearing Syk overexpression, experienced cell proliferation arrest, growth inhibition and apoptosis at a dose much lower than the remaining MCL cell lines. In B cells, Syk leads to intracellular calcium mobilisation, activation of AKT, mitogen‐activated protein kinases and NF κ B activation (Beitz et al , 1999; Cornall et al , 2000; Yokozeki et al , 2003). The BCR signalling pathway is believed to play a major role in B‐cell lymphoma growth and survival (Kuppers, 2005).…”
Section: Discussionmentioning
confidence: 99%